Effect of repetitive transcranial magnetic stimulation on anxiety symptoms in patients with major depression: An analysis from the THREE‐D trial. Issue 3 (11th December 2020) - Trevizol, Alisson P.; Downar, Jonathan; Vila‐Rodriguez, Fidel; Konstantinou, Gerasimos; Daskalakis, Zafiris J.; Blumberger, Daniel M.
Abstract: Background: Despite the advances in the use of repetitive transcranial magnetic stimulation (rTMS) for the treatment of major depressive disorder (MDD), there is relatively little information about its effect on comorbid anxiety symptoms. Methods: Data from a large randomized noninferiority trial comparing intermittent theta‐burst stimulation (iTBS) and high‐frequency (10 Hz) rTMS delivered to the left dorsolateral prefrontal cortex (HFL) were analyzed. The primary aim was assessing changes in anxiety/somatization items from the 17‐item Hamilton Depression Rating Scale (HAM‐D) and the Brief Symptom Inventory (BSI‐A), using baseline‐adjusted change with an analysis of covariance (ANCOVA), with the final scores as the outcome and baseline scores as the adjustment covariates. Results: The analytical cohort comprised 388 participants (189 in HFL and 199 in iTBS groups). From baseline to the end of the rTMS course, the combined score from the anxiety items from the HAM‐D dropped from 7.43 ( SD  = 2.15) to 4.24 ( SD  = 2.33) in the HFL group, and 7.33 ( SD  = 2.13) to 3.76 ( SD  = 2.23) in the iTBS group. The ANCOVA resulted in an effect from time ( p  < .0001), but not from group allocation ( p  = .793) or time × group interaction ( p  = .976). We observed mean changes in the BSI‐A of −3.5 ( SD  = 5.4) and −3.2 ( SD  = 4.8), with significant effect of time ( p  < .0001) in the ANCOVA, but not group allocation ( p  = .793) or group × time interaction (.664). Conclusions: Our findings suggest that both 10 Hz and iTBS may yield potential reductions in anxiety symptoms when used for the treatment of MDD. Our findings warrant future research into the effects of left‐sided rTMS on depressed patients struggling with concurrent anxiety symptoms.